The Aplication of Blended Learning to Overcome Students Learning Saturation in Arabic Learning Class XI MAN 2 Parepare - Saepudin; Hamsiah, Hamsiah; Darmawati (Al-Iftah: Journal of Islamic studies and society, 2022)
This study analyzes the "Application of Blended Learning to Overcome Student Saturation in Learning Arabic Class XI MAN 2 Parepare". Aims to find out the saturation of learning caused by learning Arabic that is not optimal. Blended learning combines face-to-face and online meeting learning to be an alternative to learning. This study uses a qualitative research method that is descriptive in nature, namely to provide an overview of the situation factually, and systematically, by collecting data, and facts about learning saturation in learning Arabic at MAN 2 Parepare. The combination of online and offline learning can produce effective and efficient learning. Effectively, blended learning is a balanced concept between increasing insight and knowledge online and increasing skills offline, while attitudes can be obtained from online and offline learning. Efficiently, students can arrange teaching materials in the form of multimedia with a wider and varied range of materials and students can easily access online materials wherever and whenever according to their needs and time availability. The application of Blended learning at MAN 2 Parepare is carried out using the SIATI MADDUPA application. The effect of using this application, in general, is that students can access all the needs of a series of students in this one application only by having a student card that has been equipped with a barcode. With this student card, students can take attendance independently and have their attendance recorded in real-time, can access library books, and can access the school's internet for free with a barcode scan. This application has just been launched, with various features in this application that can be utilized by all school stakeholders. Even so, the use of this application is not maximized because it is still being developed so that it can be optimal in its use. The implications of the whole series with various research objects based on facts, as well as various sources from all school stakeholders are very helpful in the process of writing this scientific paper.